Unveiling abietic Acid’s therapeutic potential: a narrative review on structure-activity relationship, pharmacological properties, pharmacokinetics, and toxicological considerations - Ren, Wanqing; Liu, Tongzheng; Wu, Jianlin (Frontiers in Pharmacology, 2026)
Abietic acid (AA) is a carboxylic acid and a tricyclic diterpenoid that is found in a variety of coniferous resins. Its promising natural properties have renewed interest in this substance that has been used medicinally for centuries for a range of indications including wounds, inflammation and infections. Extensive preclinical evidence over the past decade also supports its therapeutic properties. This review discusses the structure-activity relationship, pharmacological actions, pharmacokinetics and toxicology of AA. The unique molecular structure of AA, which supports a phenanthrene-like structure, a conjugated diene and carboxylic acid pharmacophore, rationalizes aspects of its wide biological effects. Preclinical research supports potentially significant anti-tumor effects in model systems through ferroptosis and cell cycle arrest, prominent anti-inflammatory activity via COX-2 inhibition and PPARα/γ activation, broad-spectrum antimicrobial activity with antibiofilm effects and hepatoprotective effects via Nrf2/HO-1. Nevertheless, clinical translation is faced with low oral bioavailability, poor aqueous solubility, and high first pass metabolism. New delivery systems such as nanoparticle formulations may hold promise in overcoming these challenges. Although its toxicological profile appears favorable, thorough pharmacokinetic studies and well-designed clinical trials are necessary. This narrative review highlights the novelty of consolidating scattered preclinical data on AA, a lesser-known natural compound in pharmacology, to increase awareness of its multifaceted therapeutic potential. Its utility lies in guiding future research toward optimized derivatives and formulations, potentially bridging traditional medicine with modern therapeutics for conditions like cancer, inflammation, and infections, while identifying key gaps for interdisciplinary efforts.